A CONCEPTUAL FRAMEWORK SUPPLY CHAIN PERFORMANCE ALONG SEVERAL SOURCING OF RISK IN SMALL MEDIUM ENTERPRISE IN MALAYSIA - Jannah Munirah Binti Mohd Noor; Akmal Aini Othman; Shatina Saat; Azila Jaini (International Journal of Accounting, Finance and Business, 2021)
Theory, framework, tools, and techniques used to analyse Small and MediumManufacturing Enterprise (SME) have often been designed for application in large Enterprise.This is predominantly the case when it comes to Supply Chain Management (SCM) and SupplyChain Risk Management (SCRM). SMEs, however, particularly in Malaysia, have uniquecharacteristics and challenge. The Covid19 pandemic has forced supply chain managementresearcher and practitioners to question is, where does supplier chain management go fromhere? What has supply chain management learned from the COVID19 crisis can applied infuture? Both in day-to-day operations and in preparation for the next global mega disasters?Are they can sustain in the marketplace after all this risk? If they can sustain what are themitigation strategy and what is the resilience strategy significant for the Small MediumEnterprise. This paper presents an initial attempt to bridge this theoretical gap the developmentof a conceptual framework for the analysis of Supply Chain Risk Management in Small MediumEnterprise in Malaysia.